Algorithms and gender: Artificial intelligence at the service of symbolic violence - Ledesma, José Osvaldo (2022)
This research shows how artificial intelligence mechanism contributes to the constitution and expansion of symbolic gender violence. Reaffirmation of this type of violence occurs through the preliminary results that artificial intelligence shows users in the use of digital platforms, which results carry algorithmic biases that operate on the basis of user search patterns.